Prestasi Belajar Bahasa Indonesia Siswa Sekolah Dasar Dapat Ditingkatkan Melalui Optimalisasi Penerapan Metode Diskusi Kelompok Kecil (Small Group Discussion) - Ambrosius Iskandar (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This classroom action research was conducted with the aim to improve Indonesian language learning achievement of III gradestudents in semester I in the 2021/2022 academic year SD Negeri 22 Lanjau after optimizing the application of small group discussions. Data collected through learning achievement tests. The collected data analyzed by quantitative descriptive statistical analysis. The results obtained from this study were Small Group Discussion Methods (Small Group Discussion) can improve student learning achievement in Indonesian. This was evident from the results obtained where the average value of Indonesian language which initially 64.21 increased to 73.77 in the first cycle and in the second cycle it increased again to reach 80.70. The number of students who were able to fulfill the KKM in the first cycle 58% increased to 95% in the second cycle. In conclusion, the optimization of the application of small group discussion methods can improve the learning achievement of Indonesian language students at VI grade students in the second semester of the 2021/2022 academic year in SD Negeri 22 Lanjau.